PROBLEMATIKA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM (PAI) PADA MASA PANDEMI COVID-19 DI SMP NEGERI 2 NGANTANG KECAMATAN NGANTANG KABUPATEN MALANG - Lailatul Mufidayatus Sholikah; Muhammad Hanif; Lia Nur Atiqoh Bela Dina (Vicratina : Jurnal Ilmiah Keagamaan, 2021)
The purpose of this research is to describe learning Islamic religious education during Covid-19 pandemic at SMP Negeri 2 Ngantang, to describe the problems of Islamic religious education learning during the Covid-19 pandemic at SMP Negeri2 Ngantang, and to describe a solution in overcoming the problems of Islamic religious education learning during the Covid-19 pandemic at SMP Negeri 2 Ngantang. This study used qualitative research methods. The procedure for data collection using the methods of observation, interviews, and documentation. In this study, implementation of Islamic religious education learning during the Covid-19 Pandemic at SMP Negeri 2 Ngantang has been running effectively even though there are various problems from the side of educators, students and the environment. Teachers try to overcome these problems by finding solution so that learning continues to run well.